The treatment of mixing in core helium burning models – II. Constraints from cluster star counts. Issue 4 (13th January 2016) - Constantino, Thomas; Campbell, Simon W.; Lattanzio, John C.; van Duijneveldt, Adam
Abstract: The treatment of convective boundaries during core helium burning is a fundamental problem in stellar evolution calculations. In the first paper of this series, we showed that new asteroseismic observations of these stars imply they have either very large convective cores or semiconvection/partially mixed zones that trap g modes. We probe this mixing by inferring the relative lifetimes of asymptotic giant branch (AGB) and horizontal branch (HB) from R 2, the observed ratio of these stars in recent HST photometry of 48 Galactic globular clusters. Our new determinations of R 2 are more self-consistent than those of previous studies and our overall calculation of R 2 = 0.117 ± 0.005 is the most statistically robust now available. We also establish that the luminosity difference between the HB and the AGB clump is Δ L_HB^AGB = 0.455 ± 0.012 . Our results accord with earlier findings that standard models predict a lower R 2 than is observed. We demonstrate that the dominant sources of uncertainty in models are the prescription for mixing and the stochastic effects that can result from its numerical treatment. The luminosity probability density functions that we derive from observations feature a sharp peak near the AGB clump. This constitutes a strong new argument against core breathing pulses, which broaden the predicted width of the peak. We conclude that the two mixing schemes that can match the asteroseismology are capable of matching globular cluster observations, but only if (i) core breathing pulses are avoided in models with a semiconvection/partially mixed zone, or (ii) that models with large convective cores have a particular depth of mixing beneath the Schwarzschild boundary during subsequent early-AGB 'gravonuclear' convection.